Investigation of Die Design Influence on Required Forces in Near-Solidus Forging of Complex Components - John Damilola Sunday; Alberto Murillo-Marrodán; Eduardo García; Carl Slater (Journal of Manufacturing and Materials Processing)
This study investigates the influence of die design parameters on forging forces and thermomechanical responses during near-solidus forging (NSF) of complex steel components. Finite element simulations using Forge NxT analyzed six die configurations varying geometry orientation, gating system design (conical, cylindrical, curvilinear), and draft angles (20° and 30°), with 42CrMo4E steel modeled at 1360 °C. Key responses including punch and lateral forces, temperature distribution, strain localization, and die stress were evaluated to assess design effects. Results showed that the gating system geometry critically controls material flow and load requirements. The conical gating design with a 30° draft angle yielded the lowest punch (141.54 t) and lateral (149.44 t) forces, alongside uniform temperature and strain distributions, which improve product quality by minimizing defects and incomplete filling. Lower lateral forces also reduce die opening risk, enhancing die life. In contrast, the base case with a 20° draft angle exhibited higher forces and uneven strain, increasing die stress and compromising part quality. These findings highlight the importance of selecting appropriate gating systems and draft angles to reduce forming loads, increase die life, and improve uniform material flow, contributing to better understanding of die design in NSF of complex steel components.